2020
DOI: 10.1177/1099636219900344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the length of basalt fibers on the shear mechanical properties of the core structure of biomimetic fully integrated honeycomb plates

Abstract: To promote the application of basalt fibers, this study investigated the effect of different fiber lengths (L f ) of short basalt fibers on the shear mechanical properties of biomimetic fully integrated honeycomb plates, which were manufactured with a short basalt fiberreinforced epoxy resin polymer composite, using a double shear experiment. The results showed that the fully integrated honeycomb plate with an L f of 6 mm had the best mechanical properties, and the shear modulus of the fully integrated honeyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The highest percentage exceeded 80% and appeared at LHP 16 , with a single layer thickness of 60 mm. This further manifested radiation as the dominant heat transfer method not only in a single-layer honeycomb panel HP at room temperature [ 21 ] but also in an LHP. The intrinsic causes of the above phenomenon are further analyzed as follows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest percentage exceeded 80% and appeared at LHP 16 , with a single layer thickness of 60 mm. This further manifested radiation as the dominant heat transfer method not only in a single-layer honeycomb panel HP at room temperature [ 21 ] but also in an LHP. The intrinsic causes of the above phenomenon are further analyzed as follows.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, we have cooperated with manufacturers [ 18 ] to jointly develop new products and construction technologies derived from hollow floors, such as BEPs for wall insulation. It has been proven that BEPs have better mechanical properties than HPs in terms of compression [ 19 ], bending [ 20 ], and shear [ 21 ]. In previous papers [ 22 , 23 , 24 , 25 ], the thermal insulation performance of BEPs was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the honeycomb plate, the beetle elytron plate (BEP), characterized by a trabecular-honeycomb core structure (Figure 1(d) and (e)), which is inspired by the three-dimensional structure of the Allomyrina dichotoma beetle forewing (Figure 1(a) to (c)), 6,7 has better mechanical properties in terms of compression, 8 energy absorption, 9 bending 10 and shear. 11 Moreover, it has been confirmed that the end-trabecular beetle elytron plate (EBEP) and grid beetle elytron plate (GBEP) have similar mechanical properties but different strengthening characteristics. Therefore, these two kinds of BEPs represent new bionic sandwich structures with better mechanical properties than honeycomb plates.…”
Section: Introductionmentioning
confidence: 98%
“…The shared mechanism of trabeculae, the synergistic mechanism of the trabecular-honeycomb structure, and the excellent mechanical properties of EBEP have been recently investigated [ 25 ]. The results proved that the mechanical properties of compression [ 26 ], energy absorption [ 27 ], bending [ 28 ], and shearing [ 29 ] of the EBEP were significantly better than those of traditional honeycomb plates. In this context, the vibrational characteristics of a 3D-printed BEP composed of aluminum were proven in a previous study [ 30 ] to be better than those of a traditional honeycomb plate.…”
Section: Introductionmentioning
confidence: 99%